Ревизия материалов по морфологии и экологии ксилофильных личинок ктырей трибы Laphriini (Diptera, Asilidae). Сообщение II. Род Laphria Mg - Кривошеина, Н.П.; Мамаев, Б.М. (Вестник зоологии, 1975)
The article is devoted to xylophilic larvae of assassin flies larvae developing in passages of various arbovorous insects (barbels, oak-borers and others). For the first time the data are presented on morphology and trophic relations of larvae of four Laphria Mg. species and additional information on 3 species of larvae of the genus under study which were slightly investigated. A determination key is compiled.